Antibiotic Resistance Genes Occurrence in Conventional and Antibiotic-Free Poultry Farming, Italy - Muhammad Farooq; Camilla Smoglica; Fausto Ruffini; Lidia Soldati; Fulvio Marsilio; Cristina E. Di Francesco (Animals, 2022)
Antimicrobial resistance is a complex and widespread problem threatening human and animal health. In poultry farms, a wide distribution of resistant bacteria and their relative genes is described worldwide, including in Italy. In this paper, a comparison of resistance gene distribution in litter samples, recovered from four conventional and four antibiotic-free broiler flocks, was performed to highlight any influence of farming systems on the spreading and maintenance of resistance determinants. Conventional PCR tests, targeting the resistance genes related to the most used antibiotics in poultry farming, along with some critically important antibiotics for human medicine, were applied. In conventional farms, n. 10 out of n. 30 investigated genes were present in at least one sample, the most abundant fragments being the tet genes specific for tetracyclines, followed by those for aminoglycosides and chloramphenicol. All conventional samples resulted negative for colistin, carbapenems, and vancomycin resistance genes. A similar trend was observed for antibiotic-free herds, with n. 13 out of n. 30 amplified genes, while a positivity for the mcr-1 gene, specific for colistin, was observed in one antibiotic-free flock. The statistical analysis revealed a significant difference for the tetM gene, which was found more frequently in the antibiotic-free category. The analysis carried out in this study allowed us to obtain new data about the distribution of resistance patterns in the poultry industry in relation to farming types. The PCR test is a quick and non-expensive laboratory tool for the environmental monitoring of resistance determinants identifying potential indicators of AMR dissemination.